Temporal analysis of protozoan lysis in a microfluidic device - Santillo, Michael F. (Lab Chip, 2009)
A microfluidic device was fabricated and characterized for studying cell lysis of Arcella vulgaris, a nonpathogenic amoeba, over time. The device contains a series of chambers which capture cells allowing them to be subsequently exposed to a constant flow of biocidal agent. With this microfluidic system, individual cells are observed as they undergo lysis. This allows high-throughput measurements of individual lysis events, which are not possible with conventional techniques. Differences in lysis and decay times for Arcella were seen at different flow rates and concentrations of benzalkonium chloride, a biocidal detergent. The efficacy of benzalkonium chloride, chlorhexidine digluconate, phenol, sodium dodecyl sulfate, and Triton X-100 were compared, revealing information on their mechanisms of action. The presented device allows cell capture, controlled exposure to chemical biocides, and observation of lysis with single-cell resolution. Observations at the single cell level give insight into the mechanistic details of the lysis of individual Arcella cells vs. the population; decay times for individual Arcella cells were much shorter when compared to a population of 15 cells.